Cardio-diabetology: New subspecialty and collaborative work to defeat the burden of deadly duo - Han Naung Tun (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2018)
Cardiovascular disease (CVD) is one of the most global threatened diseases; particularly coronary artery disease (CAD) is a major deadly attack around the world. Diabetes mellitus (DM) is associated with a 2 to 4-fold increased mortality risk from heart disease. Diabetes related microvascular complication is seemed to be a hazardous factor for cardiovascular system and likely to cause coronary arteries disease, hypertension, peripheral arteries, and carotid vessels, especially seen in the type 2 DM populations. The severity of cardiovascular complications are related to prolong hyperglycemia and the control of dysglycemia. Thus, effective glycemic control is one of the imperative aspects of the management for the prevention of CVD in diabetes. In addition, different kinds of antidiabetes agents have different mechanism of actions that has impacted to cardiovascular outcome. The benefit and risk of current anti-diabetic agents are needed to define clearly and that is needed to promote effective clinical care between cardiology and diabetology. There are multiple complications and sequelae of diabetes that requires the involvement of cardiologic expertise in the diabetes care setting in heart disease population. Therefore, the close cooperation between the cardiologist and the diabetologist is new perceptive way of care to defeat diabetes related cardiovascular complications.